Malaysia’s approach in handling covid-19 onslaught: Report on the movement control order (mco) and targeted screening to reduce community infection rate and impact on public health and economy (2020)
Malaysia recorded its first case of COVID-19 on January 24th, 2020 with a stable number of reported cases until March 2020, where there was an exponential spike due to a massive religious gathering in Kuala Lumpur. This caused Malaysia to be the hardest hit COVID-19 country in South East Asia at the time. In order to curb the transmission and better managed the clusters, Malaysia imposed the Movement Control Order (MCO) which is now in its fourth phase. The MCO together with targeted screening have slowed the spread of COVID-19 epidemic. The government has also provided three economic stimulus packages in order to cushion the impact of the shrinking economy. Nonetheless, early studies have shown that the MCO would greatly affect the lower and medium income groups, together with small and medium businesses.